Evidence of Submicroscopic Plasmodium knowlesi Mono-Infection in Remote Indigenous Communities in Kelantan, Peninsular Malaysia - Nor Diyana, Dian; Ahmad Basyir, Muhammad; Elora, Nor Azman; Nur Ashrina, Eddie; Nur Iman, Azmi; Valerie Chong, Tze Yee; Mohd Amirul Fitri A., Rahim; Mohd Bakhtiar, Munajat; Rakna, Mohd Ikhwan Mukmin Seri; Muhd Rafiq, Mohd Kasri; Ahmad Imran, Mohamed; Nuraffini, Ghazali; et al. (The American Journal of Tropical Medicine and Hygiene, 2023)
Malaysia has maintained zero cases of indigenous human malaria since 2018. However, zoonotic malaria is still prevalent in underdeveloped areas and hard-to-reach populations. This study aimed to determine the prevalence of malaria among remote indigenous communities in Peninsular Malaysia. A cross-sectional survey was conducted in six settlements in Kelantan state, from June to October 2019. Blood samples were tested for malaria using microscopy and nested polymerase chain reaction (nPCR) targeting the Plasmodium cytochrome c oxidase subunit III (cox3) gene. Of the 1,954 individuals who appeared healthy, no malaria parasites were found using microscopy. However, nPCR revealed seven cases of Plasmodium knowlesi mono-infection (0.4%), and six out of seven infections were in the group of 19 to 40 years old (P = 0.026). No human malaria species were detected by nPCR. Analysis of the DNA sequences also showed high similarity that reflects common ancestry to other P. knowlesi isolates. These findings indicate low submicroscopic P. knowlesi infections among indigenous communities in Malaysia, requiring PCR-based surveillance to support malaria control activities in the country.